Graphitic carbon nitride and carbon nanotubes modified active carbon fiber cathode with enhanced H2O2 production and recycle of Fe3+/Fe2+ for electro-Fenton treatment of landfill leachate concentrate. Issue 2 (5th January 2022) - Li, Mingran; Qin, Xia; Gao, Mingxiao; Li, Tinghui; Lv, Yue
Abstract : g-C3 N4 /CNTs/ACF with improved H2 O2 production and Fe 2+ regeneration showed an excellent performance in the treatment of landfill leachate concentrate. Abstract : The electro-Fenton (EF) technique has attracted great interest in the treatment of landfill leachate concentrate (LLC). Active carbon fiber (ACF) was modified with graphitic carbon nitride (g-C3 N4 ), carbon nanotubes (CNTs) and polytetrafluoroethylene (PTFE) through a wet ultrasonic impregnation–calcination process, which enhanced the production of H2 O2 and regeneration of active Fe(ii ) in an EF system. The experiments on physicochemical characterization demonstrated that the modified ACF was provided with more active sites and the hydrophobicity of the electrode was improved, facilitating the O2 mass transfer. Through comparison with pristine ACF, g-C3 N4 /ACF and CNTs/ACF, electrochemical experiments showed that g-C3 N4 /CNTs/ACF exhibited the best performance on the electrocatalytic activity of the oxygen reduction reaction (ORR) and electron transfer efficiency attributed to the synergetic effect of g-C3 N4 and CNTs. Fulvic acids (FA) were used to simulate LLC to investigate the effect of operational parameters on EF performance. Under optimal conditions, H2 O2 production of g-C3 N4 /CNTs/ACF reached 132 mg L −1 with an H2 O2 generation rate of 3.96 mg h −1 cm −2 and 86% FA was removed with a kinetic rate of 0.046 within 2 h. Simultaneously, the concentration of dissolved Fe 2+ in the system increased from 2.5 mg L −1 to 6.4 mg L −1 after modification, thus continuously reacting with H2 O2 to produce more ˙OH. Remarkably, an excellent EF performance was achieved with g-C3 N4 /CNTs/ACF in the treatment of LLC, where 74.7% of TOC was removed with an economical energy consumption of 5.76 kW h kgTOC −1 and biodegradability was improved significantly, as concluded from the results of UV-vis and a 3D excitation–emission matrix (EEM). After 10 cycles, H2 O2 production could still reach 120 mg L −1 and the mineralization rate remained at 66%. This work develops an efficient, cost-effective, and durable EF cathode for the treatment of LLC.